Information Security Management for Cyber Security Challenges in Smart Cities Security and Privacy - OTHMAN, AZZAM (2022)
Information security management universally needed and has become popular in our digital world. A growing proportion of human activities, such as social interactions, entertainment, shopping, and gathering information, are now mediated by digital services and devices that are needed to be protected 24/7 based on the information security triangle Confidentiality, Integrity, and Availability. Currently, there are more than 12.3 billion IoT devices connected to our digital world recording everything around us such as street cameras, smart security devices, smart refrigerators, smart watches, etc. These devices collect most of our daily time information as our health by smart watches, refrigerator needs, air condition status, GPS information, and so on. Much of our daily life activities and privacy collected by these digital devices connected to the Internet. The main objective of this research is to answer the question whether information security management can protect our daily life and privacy information to be able to live in safe life in our smart cities or not. The findings of this study suggest that lack of in-house expertise, insufficient funding, difficulty in locating right security talent, poor leadership and lack of accountability are the top cyber-security challenges. In addition, it was found that organizations are mediocrely prepared to detect, prevent and respond to cyber-threats. Furthermore, it was revealed that individuals have mediocre level of security awareness.